Low-Cost Tetraplex PCR for the Global Spreading Multi-Drug Resistant Fungus, Candida auris and Its Phylogenetic Relatives - Arastehfar, Amir; Fang, Wenjie; Badali, Hamid; Vaezi, Afsane; Jiang, Weiwei; Liao, Wanqing; Pan, Weihua; Hagen, Ferry; Boekhout, Teun (Frontiers in Microbiology, 2018)
Candida auris, Candida haemulonii, Candida duobushaemulonii and Candida pseudohaemulonii are closely related and highly multidrug resistant yeast pathogens. The high cost and low accuracy of current diagnostics may underestimate their prevalence, especially in medical resource-limited regions. In this study, we used 172 C. auris stains and its relatives and 192 other fungal strains to establish and validate a novel multiplex end-point PCR. A prospective and a retrospective clinical screenings using this assay were further performed in China and Iran respectively. We identified the first isolate of C. pseudohaemulonii in China and the first isolate of C. haemulonii in Iran from 821 clinical isolates in total, without any false positive. Animal models of C. auris and C. haemulonii were established for validation. The overall positive rates of the assay for mice blood and tissue were 28.6% and 92.9%, respectively. Compared with previously developed assays, our assay is more available and affordable to the developing countries, and may contribute to a better understanding of the epidemiology of C. auris and its relatives in these regions.